Traumatic brain injury among female offenders in a prison population: results of the FleuryTBI study. Issue 1 (21st October 2016) - Durand, Eric; Watier, Laurence; Lécu, Anne; Fix, Michel; Weiss, Jean‐Jacques; Chevignard, Mathilde; Pradat‐Diehl, Pascale
Abstract: Aim: The study was designed to estimate the prevalence of traumatic brain injury (TBI) in a French prison population of female offenders, study the variables known to be associated with TBI, and compare our results with those obtained among male offenders as described in a previous paper. Participants: All female offenders (adults and juveniles) consecutively admitted to Fleury‐Mérogis prison over a 3‐month period were included in the study. Method: During the admission procedure, female offenders were interviewed by healthcare staff using a self‐reported questionnaire. Results: In all, 100 female offenders were included. The rate of self‐reported TBI was high, with a prevalence of 21%. The first cause of TBI was violence related (35%) and a majority of female offenders with a history of TBI reported having sustained more than one TBI. When compared with those who did not report a TBI, epilepsy and use of alcohol were higher among female offenders with a history of TBI. Perceived health was significantly worse for women who reported a TBI. Conclusions: This study findings provide additional evidence that TBI among offender populations is serious and that specific actions need to be developed and implemented in correctional settings such as screening for TBI upon arrival. Abstract : The study was designed to estimate the prevalence of TBI in a French prison population of female offenders. The rate of self‐reported TBI was high, with a prevalence of 21% and the first cause of TBI was violence related.